Vaccination coverage of children with inflammatory bowel disease after an awareness campaign on the risk of infection. Issue 6 (June 2015) - Fleurier, Aude; Pelatan, Cecile; Willot, Stephanie; Ginies, Jean-Louis; Breton, Estelle; Bridoux, Laure; Segura, Jean-Francois; Chaillou, Emilie; Jobert, Agathe; Darviot, Estelle; Cagnard, Benoit; Delaperriere, Nadege; et al.
Abstract Background Children with inflammatory bowel disease are at risk of vaccine-preventable diseases mostly due to immunosuppressive drugs. Aim To evaluate coverage after an awareness campaign informing patients, their parents and general practitioner about the vaccination schedule. Methods Vaccination coverage was firstly evaluated and followed by an awareness campaign on the risk of infection via postal mail. The trial is a case–control study on the same patients before and after the awareness campaign. Overall, 92 children were included. A questionnaire was then completed during a routine appointment to collect data including age at diagnosis, age at data collection, treatment history, and vaccination status. Results Vaccination rates significantly increased for vaccines against diphtheria–tetanus–poliomyelitis (92% vs. 100%), Haemophilus influenzae (88% vs. 98%), hepatitis B (52% vs. 71%), pneumococcus (36% vs. 57%), and meningococcus C (17% vs. 41%) (p < 0.05). Children who were older at diagnosis were 1.26 times more likely to be up-to-date with a minimum vaccination schedule (diphtheria–tetanus–poliomyelitis, pertussis, H. influenzae, measles–mumps–rubella, tuberculosis) (p = 0.002). Conclusion Informing inflammatory bowel disease patients, their parents and general practitioner about the vaccination schedule via postal mail is easy, inexpensive, reproducible, and increases vaccination coverage. This method reinforces information on the risk of infection during routine visits.